A model for developing competent and self-directed tradespeople. (2nd January 2019) - Pearce, Damien
ABSTRACT: Recent research has linked the development of self-directed learning of building and construction apprentices to the quality of relationship between the apprentice and their sponsor. This relationship was found to be critical for the apprentice to develop the capacity for self-directed learning. The sponsor as a more confident or experienced other possessed both a personal and professional interest in the development of the apprentice and used their influence to create a safe learning environment within the workplace. A literature review positions self-directed learning in the context of this research and within the methodology of constructivist grounded theory. This paper discusses the importance of sponsorship to the development of self-direction and concludes with offering some suggestions about how the learning environment within the workplace may be augmented to facilitate the development of self-direction. The role and the obligations of the apprentice's sponsor are also considered in detail.